PENGARUH MODEL PEMBELAJARAN MAKE A MATCH DAN FLIPBOOK TERHADAP HASIL BELAJAR SISWA KELAS VII - Selvira Septiyanda; Laili Fitri Yeni; Reni Marlina (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2022)
This study aims to determine the effect of the Make A Match cooperative model and the Media Flipbook on student learning outcomes in the Class VII students of Class VII SMP Negeri 3 Pontianak material. The form of research was quasi-experimental with Nonequivalent Control Group Design. The research sample was class VII B (experimental class) and class VII C (control class), with the intact group sampling technique. The instrument used was a multiple choice test of 20 questions. The average score of the experimental class students 'learning outcomes was 16.89, while the average score of the control class students' learning outcomes was 15.93. Based on the results of the Mann-Whitney U test, the p value (asymp sig 2 tailed) was obtained 0.034 <0.05, where there was a difference between the learning outcomes of students who were given learning using the Make A Match cooperative model and the Media Flipbook with students who were given learning using the model. conventional learning assisted by image media. Based on the Effect Size, the Make A Match cooperative learning type and the Media Flipbook gave a value of 0.74 in the medium category and contributed 26.42% in improving the learning outcomes of class VII students of SMP Negeri 3 Pontianak on the Classification of Living Things.